Criminal Justice Responses to Trafficking in Persons - Ngo Thi Minh Huong; Giao Cong Vu (University of Jember, 2023)
Human trafficking is a domestic and transnational crime that poses complex law enforcement challenges to all nations. Vietnam is particularly affected due to rapid growth in labour migration and international tourism. The presumption of law makers is that by improving the criminal justice response to trafficking in persons (TIP), its incidence within the country and beyond its borders will decrease. Inherent in this premise is the assumption that strong legal sanctions deter would-be traffickers. This paper describes Vietnam’s criminal justice responses to human trafficking with reference to the legal framework and institutions. Barriers and challenges in implementing the ASEAN Convention on Trafficking in Persons (ACTIP), and the underlying reasons why the current response is inadequate in addressing TIP are identified with a focus on issues associated with victims and trials. The paper argues that Vietnam needs to increase efforts to meet its obligations and standards as set out in the United Nation’s Recommended Principles and Guideline on Human Rights and Human Trafficking and ACTIP. In particular, prosecution of traffickers and the protection of victims need to be prioritised. Keywords: Human Trafficking, Human Rights, Labor Migration, Criminal Justice, Vietnam